SOA-based enterprise integration [ a step-by-step guide to services-based application integration - Roshen, Waseem , 1951- (New York : McGraw-Hill, 2009)
A practical guide to implementing Service-Oriented Architecture (SOA) within the enterprise
1. 1. Introduction -- 2. Evolution of integration patterns -- 3. Service-oriented architecture-based integration -- 4. Integrating existing applications -- 5. Understanding and developing web services
Includes bibliographical references (p. 333-336) and index
Keywords: Enterprise application integration (Computer systems); Management information systems; Service-oriented architecture (Computer science)